SOSAS Study in Rural India: Using Accredited Social Health Activists as Enumerators - Srivarshini Cherukupalli (Ubiquity Press, 2019)
Background: Global estimates show five billion people lack access to safe, quality, and timely surgical care. The wealthiest third of the world’s population receives approximately 73.6% of the world’s total surgical procedures while the poorest third receives only 3.5%. This pilot study aimed to assess the local burden of surgical disease in a rural region of India through the Surgeons OverSeas Assessment of Surgical Need (SOSAS) survey and the feasibility of using Accredited Social Health Activists (ASHAs) as enumerators. Material and Methods: Data were collected in June and July 2015 in Nanakpur, Haryana from 50 households with the support of Indian community health workers, known as ASHAs. The head of household provided demographic data; two household members provided personal surgical histories. Current surgical need was defined as a self-reported surgical problem present at the time of the interview, and unmet surgical need as a surgical problem in which the respondent did not access care. Results: One hundred percent of selected households participated, totaling 93 individuals. Twenty-eight people (30.1%; 95% CI 21.0–40.5) indicated they had a current surgical need in the following body regions: 2 face, 1 chest/breast, 1 back, 3 abdomen, 4 groin/genitalia, and 17 extremities. Six individuals had an unmet surgical need (6.5%; 95% CI 2.45%–13.5%). Conclusions: This pilot study in Nanakpur is the first implementation of the SOSAS survey in India and suggests a significant burden of surgical disease. The feasibility of employing ASHAs to administer the survey is demonstrated, providing a potential use of the ASHA program for a future countrywide survey. These data are useful preliminary evidence that emphasize the need to further evaluate interventions for strengthening surgical systems in rural India.